The use of oxidative stress biomarkers in the study of exposure to pesticides: a review - Teixeira da Silva, Heberson; Silva Souza, Kimberly; Trevisan, Kaynara; Silveira Tolentino Júnior, Dilceu; Aversi-Ferreira, Tales Alexandre (Revista Ciências da Saúde Ceuma, 2023)
The extensive use of chemical compounds in agriculture has been related to the occupational exposure of farmers, in addition to environmental degradation and contamination. Such factors can potentiate the imbalance between oxidant and antioxidant compounds, thus allowing the excessive production of reactive oxygen species, which can damage biomolecules and lead to various diseases, including Alzheimer’s and cancer. To correlate the toxic effects with exposure to pesticides, oxidative stress biomarkers have become a viable alternative, as they are more stable, specific, and sensitive molecules, with greater measurement capacity, being able to express normal and pathological biological processes or pharmacological responses to therapeutic interventions. Thus, this work aimed to evaluate the application of the use of oxidative stress biomarkers in the study of exposure to pesticides. After reviewing the literature in online databases (PubMed, Science Direct, Web of Science, and Google Scholar), it was possible to conclude that different parameters have been used as fundamental tools during all stages of risk assessment after exposure to pesticides.